Dinamika Sistem Moneter Internasional dan Dampaknya Terhadap Stabilitas Ekonomi Global - Faiz Afifi; Ahmad Radid Lingga; Muhammad Arfan (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The international monetary system has undergone significant changes, from the Gold Standard and Bretton Woods to the floating exchange rate system. Each change has had a major impact on global economic stability, international trade, and the flow of world capital. In the modern era, exchange rate volatility has become a primary challenge for both developing and developed countries. On the other hand, the Islamic economic perspective offers an approach based on justice and monetary stability through instruments such as the dinar and dirham, as well as the prohibition of interest (riba). This study aims to analyze the dynamics of the development of the international monetary system and its implications for global economic stability, as well as to assess the relevance of Islamic views in creating a stable monetary system. The research method uses a literature review of related journals and books. The analysis shows that global monetary instability is influenced by the floating exchange rate system, speculation, and the monetary policies of developed countries. Therefore, a comprehensive understanding of the dynamics of the international monetary system is essential in formulating adaptive and stable economic policies.